Gerakan Literasi Sekolah: Upaya Meningkatkan Literasi Dasar Siswa - Ikhwanun, Muhammad; Ghany Hayudinna, Hafizah (Indonesian Journal of Islamic Elementary Education, 2021)
One of the government's efforts to foster a literacy culture is through the launch of the National Literacy Movement (GLN) which then divided into literacy movements for schools, families, and communities. This study aims to describe the implementation of the school literacy movement program at MIS Karanganyar 02, Kecamatan Tirto, Kabupaten Pekalongan along with the supporting and inhibiting factors. This study uses a qualitative research approach with descriptive analysis methods. Collecting data through observation, interviews, and documentation studies. Data analysis through the stages of data collection, data reduction, data presentation, and concluding. The results of this study indicate that the implementing school literacy movement are the procurement of libraries and reading books, reading activities before class starts, writing reading results, library visits, and reading corners. Factors that support the implementation of the program are awareness of school residents towards literacy culture, availability of libraries and reading corners, active participation of school residents and parents of students, while factors that hindered the implementation were the limited complementary facilities in the library, student boredom with reading due to limited book collections, lack of support from top-level policymakers, and the COVID-19 pandemic.